SEASONALITY OF THE LEAF MINER, LEVEL OF PREDATION AND TEMPORAL OCCURRENCE OF RUST CORRELATED TO ABIOTIC FACTORS - B. M. R. Melo (Scientific Electronic Archives, 2018)
The coffee leaf miner and a rust are considered as major diseases that are able to reduce productivity in coffee plantations. These agents are influenced by abiotic factors, and their occurrence may suffer oscillation over the years. The objective of this study was to evaluate the seasonal fluctuation of the coffee leaf miner, incidence of coffee prediction and rust, correlated with abiotic factors. The study was performed IFSULDEMINAS-Campus Inconfidentes, in a coffee crop of the cultivar Rubi. A sample for a rust and a coffee leaf miner, in addition to the middle and upper third of the plants, totaling 42 plants in the study area. At the same sampling point, perform soil analysis to correlate nutrients as studied variables. The Pearson correlation of the biotic variables was performed with a precipitation and fertility, a rate of 1 and 5% probability. It was verified that the rust cycle alternated its incidence for the same period in different years and the miner showed behavior coincident to the driest periods of the year. Data not available on precipitation data and number of mines. These diseases had no significant correlation with the fertility parameter. The coffee leaf miner yielded higher rates of occurrence in June and December of 2014. It was concluded that the percentage of coffee leaf miner was higher in the months with lower rainfall indices or no longer summer period; What is it you want to know about the one-time development that may have been influenced by the nearby woods under study and the rust alternated the peaks of occurrence for the two autumners, correlating with a precipitation.